Enterprise architecture for strategic management of modern IT solutions - Iyamu, Tiko (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2022)
'This book provides guidance on how to employ enterprise architecture (EA) in deploying and managing information technology (IT) solutions from the perspectives of pragmatic strategies. It uses sociotechnical theories such as actor-network theory (ANT) and structuration theory (ST) as lenses to examine challenges and complexities of EA'--
Includes bibliographical references and index.
Keywords: Computer network architectures